Surface Finishing Theory and New Technology - Yang, Shengqiang (Springer Berlin Heidelberg, 2018)
This book focuses on the theory and techniques of free abrasive tool finishing technology. Providing analytical methods and practical technical references for the engineers involved in surface-finishing processes, it significantly contributes to improving part quality and performance while also promoting further developments in surface finishing technology. Combining a highly systematic approach, readability and novel content, it is a valuable resource for researchers and graduates working in mechanical engineering fields, especially in surface finishing.